If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(2x + 5) = 27 + 3x Reorder the terms: 8(5 + 2x) = 27 + 3x (5 * 8 + 2x * 8) = 27 + 3x (40 + 16x) = 27 + 3x Solving 40 + 16x = 27 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 40 + 16x + -3x = 27 + 3x + -3x Combine like terms: 16x + -3x = 13x 40 + 13x = 27 + 3x + -3x Combine like terms: 3x + -3x = 0 40 + 13x = 27 + 0 40 + 13x = 27 Add '-40' to each side of the equation. 40 + -40 + 13x = 27 + -40 Combine like terms: 40 + -40 = 0 0 + 13x = 27 + -40 13x = 27 + -40 Combine like terms: 27 + -40 = -13 13x = -13 Divide each side by '13'. x = -1 Simplifying x = -1
| (x+9)(x+2)=2x | | -8(2n-1)=104 | | 20=6-7x-7 | | 99=2n-5(3n+1) | | 6(2x-8)=3(3x-9) | | -8(6m-6)-8m=440 | | x^2+7x+K=0 | | -(156x-13)= | | hg(x)=3.08(x)sqrt+18.97 | | 232=4(8n-6) | | 100=4(4-3x) | | -(156-13)= | | 95=5(4-3n) | | 2.28x-.8=2x+1.8 | | Hg(x)=3.08(52)sqrt+18.97 | | -5(-1-2p)+5p=95 | | .8x+.2=.6x+-10 | | 3x-7-x=5x+14 | | 6y-10=2+4y | | 5x-11=4x+7 | | -217=-6(-6v-6)-1 | | 6(7+3x)=150 | | 0=-5n-2m | | 18x+21=10x+90 | | -317=3+5(8k-8) | | 9y-3=4+2y | | X=3xj-4 | | 4x+7(1-5x)=-210 | | (-9,2)(-10,-4)= | | 4x^2+4x+9=0 | | 7m=5+8m | | 9t-14=-26+5t |